Coordinated control of building loads, PVs and ice storage to absorb PEV penetrations. (February 2018) - Sehar, Fakeha; Pipattanasomporn, Manisa; Rahman, Saifur
Highlights: Developed load control strategy makes PEV penetration transparent to the grid. Developed strategy is applicable to any type, size and number of commercial buildings. Developed strategy improves the distribution feeder's performance. Abstract: Plug-in Electric Vehicles (PEVs) are active loads as they increase the distribution network's demand during charging and can have potential impacts on the network. This study discusses the impact of PEV charging on a distribution feeder serving commercial customers and proposes a mitigation strategy to make PEV penetration transparent to the grid. The proposed strategy relies on coordinated control of major loads in demand responsive commercial buildings, ice storage, along with strategically deployed solar photovoltaic (PV). A real world electrical distribution feeder serving a number of commercial buildings is used for analysis purposes. Rather than looking at individual building's economic benefits, the proposed approach considers overall technical and economic benefits of the whole distribution network, focusing on enhancing distribution-level load factor and reducing feeder losses. Results indicate that by performing load control in selected commercial buildings, along with utilizing capability of existing ice storage units and strategically deployed PV, the proposed approach can absorb 100% PEV penetration, and result in 13.4% decrease in the peak load; 10.9% improvement in the load factor; and 11.6% reduction in feeder losses. Sensitivity analysis shows that both load control and PV are needed to absorb any PEV penetration above 50% level.